Frames and political choice in Scottish election campaigns - Jakusné Harnos, Éva; Gergi-Horgos, Mátyás (LingBaW. Linguistics Beyond and Within, 2022)
The paper presents interdisciplinary research using the framework of cognitive linguistics based metaphor theory and nationalism studies of political science. Frames of movement are placed under scrutiny during the discourse analysis of the 2016 and 2021 election manifestos of the Scottish National Party and social media posts. In relation to metaphors of movement, images describing the future of an independent Scotland are also detected. The authors attempt to analyse and interpret findings both from the perspective of cognitive linguistics and ethno-symbolism. Apart from the texts of the manifestos, the timeframe of the research involved social media posts two months preceding and two months following the elections in both cases. Methodology was issue-driven and computer assisted but supervised: key words linked to movement were extracted from the manifestos and clustered. Their occurrence and frequency in the social media posts was checked. In the qualitative analysis phase, messages of the manifestos and of the posts were contrasted in order to answer our research question what kind of persuasive political discourse was used when options for the citizens were outlined.